Muslims' Conquests in Qafqaz - Sajjad Hosseini; Ja'far Aqazadeh (تاریخ اسلام, 2011)
Following the defeat of Iranians in the battle of Nahavand (21 A.H), in order to take the opportunity of a united defense from Iranians, Muslims were ordered by Omar to attack the Iranian states one after the other. In line with this policy, and following the conquest of Azerbaijan, the Arabian Muslims, moved towards Qafqaz and conquered it as well. The first Islamic conquests in Qafqaz has been done in four sporadic phases from the caliphate of Omar until the end of Muawiah's government, and in the era of each caliph, it has been pursued through a particular method and approach based on general policies of the caliph of time. In this period, the Muslims could reach the areas of Qafqaz previously being under the control of Sassanid government, but beyond Sassanid borders, they confronted with the severe resistance of Khazars and consequently the conquests stopped. In this research, it has been investigated the first conquests of Muslims in Qafqaz from caliphate of Omar until the end of caliphate of Muawiah as well as the issues such as the sort of conquests, the manner of their commandment and organization, the effect of the geography of area on the trend of conquests, the reaction of rulers and citizens of area towards the armies of Islam.